KETENGIKAN HIDROLISIS TEPUNG IKAN SEBAGAI BAHAN PAKAN PADA BERBAGAI WAKTU PENYIMPANAN - Muhammad Ilham Tajuddin Tajuddin; M. Fadhlirrahman Latief Latief; Abdul Alim Yamin Yamin; Ichlasul Amal Amal; Jasmal A Syamsu Syamsu (AVES: Jurnal Ilmu Peternakan, 2022)
The study aims to observe the effect of storage time on the hydrolytic rancidity of fish meal as source of protein in animal feed. This study used a completely randomized design with four treatments and four replications. The arrangement of the fish meal storage time treatments were T0: 0 weeks, T1: 2 weeks, T2: 4 weeks and T3: 6 weeks. Temperature and humidity were measured during storage in warehouse. Parameters measured were moisture and free fatty acid. The results showed that fish meal which has been stored at different times was significantly affecting (P<0.05) on moisture and free fatty acids. The average of temperature and humidity during storage (0 - 6 weeks) were 29-30oC and 60-76%. The highest moisture was 17.38% obtained in the T3 and the highest free fatty acid content was obtained at 4.30%.